UPAYA MENINGKATKAN KEAKTIFAN SISWA PADA MATA PELAJARAN IPAS MATERI BUMIKU SAYANG, BUMIKU MALANG MELALUI MEDIA KARTU DOMINO DI KELAS V SDN SUKUN 2 KOTA MALANG - Fransiska Yasinta Din Ebo; Gutama, Andika; Hidayat, Ahmad Rifki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low level of active participation among fifth-grade students at SDN Sukun 2 Malang City in learning natural and social sciences (IPAS), caused by the dominance of conventional methods and the use of less varied instructional media. The main objective of this study was to describe the implementation of domino card media and to enhance students’ learning activeness on the topic “Bumiku Sayang, Bumiku Malang”. The research method employed was Classroom Action Research (CAR) using the Kemmis & McTaggart model, conducted in two cycles. The research subjects consisted of 29 students from class VA. Data were collected through direct observation using an activeness assessment rubric and the distribution of student response questionnaires. Data analysis was carried out descriptively and quantitatively to identify trends in the improvement of student engagement across each meeting. The results indicated a significant transformation in student activeness. In the pre-cycle and the beginning of Cycle I, student activeness fell into the “Low” category, with an average percentage of 35.17%. Following the refinement of instructional actions and optimization of domino card media use, student activeness increased dramatically in the final meeting of Cycle II, reaching 86.72% and classified as “Excellent”. This improvement was further corroborated by the student response questionnaire results, which reached 85.59%, indicating that game-based media were effective in creating an interactive, concrete, and enjoyable classroom atmosphere. It can be concluded that the implementation of domino card media successfully transformed students’ roles from passive listeners into enthusiastic learning subjects who actively engage in discussion, questioning, and collaboration.